THALIB, A. 2002. Effect of additional of microbial growth factors combined with and without microbe preparate on growth performance of Etawah-cross goat. JITV 7(4): 220-226. - thalib, Amlius (Indonesian Journal of Animal and Veterinary Sciences, 2002)
Effect of microbial growth factors (FPM) combined with and without microbe preparate (SM) on growth of Etawah-crossgoat has been conducted for 14 weeks, including 2 weeks of adaptation period. Animals used were 24 male goats of Etawahcross (PE) with a mean liveweight of 17.73 Â± 1.80 kg. The animals were randomly distributed into 3 treatment groups. Eachgroup consisted of 8 animals. All animals were fed elephant grass (ad lib.) + concentrate containing 16% crude protein (1.0% oflive weight) as basal diet. The treatment groups were : I. Control (K); II. K + FPM; III. K + SM + FPM. Measurements recordedwere: feed consumption, average daily gain (ADG), dry matter digestibility (in vitro and in vivo DMDs), as well as rumenecosystem. All animals were placed in metabolism cages for 2 weeks for determination of in vivo DMD. The results showed thatFPM combined with and without SM improved the performance of both rumen ecosystem and host animals. Compared tocontrol, combination of FPM with SM increased the following parameters significantly (P<0.05): ADG (55 vs. 36 g); DMI (645vs. 609 g head-1 day-1); in vivo DMD (74 vs. 69%); FCR (12 vs. 17); in vitro DMD (49 vs. 46%); colony number of bacteria percell number of protozoa (3.09 x 104 vs. 1.12 x 104); VFA content (3.53 vs. 2.82 mg ml-1); NH3-N content (68 vs. 56 mg l-1); pH(6.78 vs. 6.65). Microbe preparate enhanced the effect of FPM on VFA content so that the combination of FPM and SM(treatment III) significantly increased the VFA content as compared to the control (P<0.05).Key words: Microbial growth factor, microbe preparate, etawah-cross goat